An Experimental Study of the Effect of Different Blending Ratios of Dual and Triple Fuel Mixtures (Gasoline-Hydrogen-Ethanol) on Laminar Flame Speed - Obayes, Oras Khudhayer; Shahad, Haroun A. K. (Journal of Petroleum Research and Studies, 2022)
Abstract In a centrally ignited constant volume chamber, an experimental research on the laminar flame speed of premixed gasoline/ethanol/hydrogen/air mixtures is undertaken at varied initial pressures (0.1-0.3 MPa), constant initial temperature (593 K), and variable equivalency ratios (0.75-1.5). The mixing method is based on the energy replacement principle, and various component blending ratios are tested. This has necessitated the construction of a specific laboratory experimental equipment. The flame speeds are measured using the Shelerian photography technique using a high-speed camera. The results reveal that adding hydrogen to dual fuel mixtures has a considerable impact on stretched laminar flame speed. The stretched laminar flame speeds for 20 percent H2-80 percent G, 40 percent H2-60 percent G, and 60 percent H2-40 percent G are 3.71 m/s, 7.329 m/s, and 11.0267 m/s, respectively, at 0.1 MPa initial pressure and stoichiometric mixture. For 20 percent H2-80 percent G, 40 percent H2-60 percent G, and 60 percent H2-40 percent G mixtures, the un-stretched flame speed at atmospheric pressure and stoichiometric is computed and found to be 1.23 m/s, 3.67 m/s, and 7.093 m/s, respectively. When the initial pressure is increased, both stretched and un-stretched flame rates drop. " The results of the triple fuel mixes demonstrate that the influence of ethanol addition on the stretched laminar flame speed is significant at constant hydrogen blending ratios, with 2.24 m/s at 20% H2-16% E-64 percent G and 2.68 m/s at 20% H2-32 % E-48 % G at 0.1 MPa for stoichiometric mixture. For dual fuel combinations, the effect of starting pressure on stretched and un-stretched flame speeds is the same. Where the flame speed has a maximum value for stoichiometric combustion, the equivalence ratio has a greater effect on flame speed. "